Synergy between callous–unemotional traits and aggression in preschool children: Cross-informant and cross-cultural replication in the UK Wirral Child Health and Development Study, and the Colombian La Sabana Parent–Child Study. (23rd August 2022) - Obando, D.; Hill, J.; Sharp, H.; Pickles, A.; Fisher, L.; Wright, N.
Abstract: Incremental prediction of aggression from callous–unemotional (CU) traits is well established, but cross-cultural replication and studies of young children are needed. Little is understood about the contribution of CU traits in children who are already aggressive. We addressed these issues in prospective studies in the United Kingdom and Colombia. In a UK epidemiological cohort, CU traits and aggression were assessed at age 3.5 years, and aggression at 5.0 years by mothers ( N = 687) and partners ( N = 397). In a Colombian general population sample, CU traits were assessed at age 3.5 years and aggression at 3.5 and 5.0 years by mother report ( N = 220). Analyses consistently showed prediction of age-5.0 aggression by age-3.5 CU traits controlling for age-3.5 aggression. Associations between age-3.5 CU traits and age-5.0 aggression were moderated by aggression at 3.5 years, with UK interaction terms, same informant, β = .07 p = .014 cross-informant, β = .14 p = .002, and in Colombia, β = .09 p = .128. The interactions arose from stronger associations between CU traits and later aggression in those already aggressive. Our findings with preschoolers replicated across culturally diverse settings imply a major role for CU traits in the maintenance and amplification of already established aggression, and cast doubt on their contribution to its origins.